(untitled) (Raparin Journal of Humanities (RJH), 2025)
The impact of the US monetary policy and the US macroeconomic variables, on the stock market specifically in relation to the Dow Jones Industrial Average (DJIA), is a subject of ongoing debate. This paper seeks to investigate and examine the consequences of changes in monetary policy and some macroeconomic variables in the United States on the US stock market (only DJIA was selected) for the period of January 2017 to June 2023. By analyzing these relationships across different time frames, this research seeks to provide a comprehensive understanding of how various US monetary and US macroeconomic factors have influenced the stock market’s behavior, corporate performance, and overall market trends, thus contributing to a deeper understanding of the interactions between central bank actions and financial markets and performance in the context of a significant global crisis. The Vector Error Correction Model (VECM) was used to study the short-run dynamics as well as the long-run relationship between the DJIA index and the five selected macroeconomic variables from the US economy. It is found that the coefficient of error correction term is (-0.225), indicating an annual adjustment of approximately 22.5 per cent towards the long-term equilibrium. This guarantees the existence of a stable long-run relationship between the variables. However, in the short-run, all selected explanatory variables do have a relationship with the DJIA index except real gross domestic product (RGDP) which is statistically insignificant which means RGDP does not have a short-run relationship with DJIA index.